Personhood, Relational Ontology, and the Trinitarian Politics of Eastern Orthodox Thinker Christos Yannaras. Issue 4 (19th May 2019) - Cole, Jonathan
ABSTRACT: Eastern Orthodox political theology has not received sufficient attention by the largely Protestant- and Catholic-dominated field of political theology. One of the Orthodox world's most important thinkers, Christos Yannaras, who has written extensively on politics, is relatively unknown amongst English-speaking Protestant and Catholic theological circles because his substantive work on politics is only available in Greek. This essay provides an introduction to one of Yannaras' most important works on political theology, The Inhumanity of Right, which has not been translated into English . Yannaras approaches politics through his person-centric anthropology and relational ontology, viewing the purpose and goal of politics as "authentic existence" in communion with the Trinitarian God. The essay seeks to demonstrate, via Yannaras' political thought, that Orthodox theologians bring a unique perspective to common political problems and challenges and that the field of political theology would be enriched from a deeper engagement with Orthodox political theology.